Mata Pencaharian (Pertanian/Perkebunan) Di Dama Gadang - Fitria Ardely; Della Arnelia Putri; Fadhlurrahman Azizi; manaruko, rino; Ridwan, Ahmad; Rozi, Fachrul; Muhammad Fauzan Auliandi; Dita Yosephine Situmorang (Universitas Negeri Padang, 2024)
Dama Gadang, an area rich in natural beauty and agricultural potential, has long been the center of attention in the fields of agriculture and plantations. This article investigates various aspects of livelihoods in agriculture and plantations in Dama Gadang. Through field surveys, interviews, and secondary data analysis, this article analyzes various factors that influence livelihoods in this area.